A "functional biopsy" of muscle properties in sprinters and distance runners - Crowther, G. J.; Jubrias, S. A.; Gronka, R. K.; Conley, K. E. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: Fast- and slow-twitch human muscle fibers exhibit large (two- to threefold) differences in metabolic enzyme activities and contractile economy. We asked whether comparable flux differences are evident in the muscles of athletes specializing in extremely different (i.e., sprint and long-distance) running events. METHODS: We took an in vivo "functional biopsy" of the ankle dorsiflexor muscles of 17 members of a university track team by using (31)P magnetic resonance spectroscopy. Ten sprinters (SPR) and seven distance runners (DIS) performed rapid isometric dorsiflexions against the resistance of a plastic foot holder. The contractile cost of exercise and glycolytic flux were calculated from changes in pH, [PCr], and [P(i)] during ischemic exercise, and oxidative capacity was calculated from PCr recovery kinetics after aerobic exercise. RESULTS: Contractile costs were 47% higher in SPR than in DIS, whereas oxidative capacities were 52% higher in DIS than in SPR. Surprisingly, glycolytic ATP production was similar in the two groups. CONCLUSION: The muscles of SPR and DIS exhibit clear differences in energetic properties, but these differences are smaller than the two- to three-fold variations seen in the properties of individual muscle fibers.